A dithiocarbamate anchoring group as a flexible platform for interface engineering - Sauter, Eric; Nascimbeni, Giulia; Trefz, Daniel; Ludwigs, Sabine; Zojer, Egbert; Wrochem, Florian von; Zharnikov, Michael (Physical chemistry, chemical physics, 2019)
The molecular organization and electronic properties of dithiocarbamate (DTC) anchored self-assembled monolayers (SAMs) linked to Au(111) substrates are studied by a combination of X-ray photoelectron spectroscopy (XPS), near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, and state-of-the-art density functional theory calculations. For that, several piperidine/piperazine precursors with different architecture and substitution patterns are selected. The presented data show that the DTC anchor provides a useful building block for monomolecular self-assembly on coinage metals with both sulfur atoms bonded to the substrate in a way similar to what is usually observed for the more commonly applied thiolate docking group. The combination of the DTC group with the quite flexible piperidine/piperazine cyclic linkers results in a dense molecular packing with an upright orientation of the terminal moieties. The latter comprise phenyl rings bearing various substituents, which enables tuning the interfacial dipole over a wide range. Simulations on two prototypical DTC-docked SAMs help to better understand the experimental observations and provide insight into the local origin of the SAM-induced shifts in the electrostatic energy. In particular, a comparison of measured and simulated XP spectra reveals the significant contribution of the DTC group to the interfacial dipole.